(NrUSSKIJ GLAGOL (B((NW SOPOSTAWITELXNOM OSWE]ENII(B) :s (NmEVWUZOWSKIJ SBORNIK NAU^NYH TRUDOW (B/s - (NlOPU[ANSKAQ(B, (NsOFIQ pETROWNAs; (NbORISOWA(B, (Nm(B.(Nb(B.s; (NiWANOW(B, (Nw(B.(Nw(B.s ((NwOLGOGRAD (B:s (NiZD(B-(NWO wOLGOGRADSKOGO GOS(B. (NUN(B-(NTA(B.s, 1988)
(NbIBLIOGR(B. (NW PRIME^(B. (NW KONCE ST(B.s
(NmIN(B-(NWO WYS[(B. (NI SRED(B. (NSPEC(B. (NOBRAZ(B. (Nrsfsr wOLGLGRAD(B. (NPOLITEH(B. (NIN(B-(NTs
(NwOLGLGRAD(B. (NgOS(B. (NuN(B-(NTs
Keywords: (NaNGLIJSKIJ QZYKs; (NgLAGOL W ANGLIJSKOM QZYKEs; (NgLAGOL W RUSSKOM QZYKEs; (NrUSSKIJ QZYKs